Participation in Courts and Tribunals Concepts, Realities and Aspirations. - Jacobson, Jessica, 1966- (Bristol University Press, 2020)
Available Open Access under CC-BY-NC licence Effective participation in court and tribunal hearings is regarded as essential to justice, yet many barriers limit the capacity of defendants, parties and witnesses to participate. Featuring policy analysis, courtroom observations and practitioners' voices, this significant study reveals how participation is supported in the courts and tribunals of England and Wales. Including reflections on changes to the justice system as a result of the COVID-19 pandemic, it also details the socio-structural, environmental, procedural, cultural and personal factors which constrain participation. This is an invaluable resource that makes a compelling case for a principled, explicit commitment to supporting participation across the justice system of England and Wales and beyond. Available Open Access under CC-BY-NC licence Effective participation in court and tribunal hearings is regarded as essential to justice, yet many barriers limit the capacity of defendants, parties and witnesses to participate. Featuring policy analysis, courtroom observations and practitioners' voices, this significant study reveals how participation is supported in the courts and tribunals of England and Wales. Including reflections on changes to the justice system as a result of the COVID-19 pandemic, it also details the socio-structural, environmental, procedural, cultural and personal factors which constrain participation. This is an invaluable resource that makes a compelling case for a principled, explicit commitment to supporting participation across the justice system of England and Wales and beyond.
Court reform, the COVID-19 pandemic and court user participation
Keywords: Criminal procedure -- England.; Criminal procedure -- Wales.; Trial practice -- England.; Trial practice -- Wales.; Criminal courts -- England.; Criminal courts -- Wales.; Procédure relative au procès -- Angleterre.; Procédure relative au procès -- Pays de Galles.; Tribunaux criminels -- Angleterre.; Tribunaux criminels -- Pays de Galles.; LAW / Courts.; Criminal courts; Criminal procedure; Trial practice; England; Wales